Molecular Identification and Genetic Variation of Rattus Species From Oil Palm Plantations of Malaysia Based on Mitochondrial Cytochrome Oxidase Subunit I (COI) Gene Sequences - Nasir, Mohamad Harris; Bhassu, Subha; Mispan, Muhamad Shakirin; Bakar, Sazaly Abu; Jing, Khoo Jing; Omar, Hasmahzaiti (Zoological science, 2022)
Rats ( species) are the most notorious vertebrate pests in Malaysian oil palm plantations. Although many studies have been conducted on Asian rats, little attention has been paid to their species composition and phylogenetic relationships in oil palm plantations in Peninsular Malaysia. We determined the mitochondrial cytochrome oxidase subunit I (COI) gene sequence (708 bp) for 216 individual rats collected from five oil palm plantations in Peninsular Malaysia. Phylogenetic analysis in conjunction with comparison with sequences from the nucleotide sequence database revealed five distinct lineages in the Malaysian oil plantations: , , , , and a taxon corresponding to the Malayan house rat, which was most frequently observed (∼50%). The last taxon has traditionally been classified as a synonym of ( ) or , but our phylogenetic analysis placed it as an independent lineage, which is not particularly closely related to or , and which we refer to as . The construction of the network showed that there is considerable genetic variation within the lineages of and , suggesting that these two species are native to the Malay Peninsula.